Internet censorship in Turkey - (:unkn) unknown (ALEXANDER VON HUMBOLDT INST INTERNET & SOC, 2015)
Turkey passed an internet censorship law in 2007 with the declared objective of protecting families and minors (Akdeniz, 2010). It established a unit within the regulator BTK (Information and Communication Technologies Authority) responsible for imposing bans and blocks on websites based on nine catalogue crimes defined by other national laws (Akgiil 2008, 2009a, 2000). As of May 2015, 80,000 websites were banned based on civil code related complaints and intellectual property rights violations, reports the independent website Engelliweb. Blocking decisions rendered by penal courts are enforced even when they are based on grounds other that the nine catalogue crimes - such as terrorism, organised crime and crime against the state. Passed in parliament while ignoring the pleas of NGOs and of the internet sector, the Internet Law No. 5651 has since been used to temporarily ban popular platforms such as Blogger, Last.fm, Vimeo, Wordpress and YouTube. At the same time, some blocking decisions by the courts (e.g., Google and Facebook) were not enforced by the authorities. Since its introduction, the European Court of Human Rights has ruled that Law No. 5651 (Council of Europe, 2011) is against the European Convention on Human Rights (ECHR, 2013). This article provides an overview of internet censorship and its social background in Turkey.
Keywords: Censorship; Freedom of information; Filtering; Internet blockings; Law No. 5651